PENGEMASAN TARI GUEL DALAM BENTUK KARTU POS SEBAGAI MEDIA PEMBELAJARAN - Suciati Simah Bengi; Dilinar Adlin (Gesture: Jurnal Seni Tari, 2018)
Abstract-This study discusses Guel dance learning media created in the form of postcards. Aims to be able to direct students in identifying, appreciating, and expressing dances of the Gayo area, especially Guel dance. Theories used in the research of packaging theory according to Cahyorini and Rusfian (2011: 28), theory of learning media according to Heinich in Susilana (2016: 06), and graphic media theory according to Susilana and Riyana (2016: 14) Packaging is a theory used for graphic design, in terms of producing the product, and the image media in the form of postcards used to make Guel dance material as a learning medium. The time of the study was conducted from August to October 2017. The research site was at Sanggar Renggali Jalan Merah Mege Hakim Bale Bujang Laut Tawar, Central Aceh District. The population of several artists Gayo and all members of Sanggar Renggali because learning Guel dance is a dance learning materials in schools in Takengon and Samples are 2 people Gayo artists and 2 dancers dance Guel. Data collection techniques include observation, interview, literature study, and documentation, and then analyzed by qualitative descriptive method. Based on research that has been done Guel dance is a tradition dance Gayo community that has been used as learning materials in the schools of Middle Secondary in Central Aceh district. Guel dance which is packed in the form of postcards as a medium of learning with menggunkana first step of planning is preparing the material, determining the location, selection of dancers, and prepare the facilities and infrastructure. The second step of implementation is taking photos, editing process, then the last step is the completion of postcards and final writing. And produces packaging of learning media of Guel dance that is in the form of postcard.  Keywords: Packaging, Guel Dance, Postcard Media